Effectiveness of Tuberculosis Financing on Reducing Tuberculosis Incidence in Asia and Africa: A Systematic Review - Salma Nusaiba; Budi Hidayat; Mufti As Siddiq M Irzal; Anggie Hardiyanti; Jihannisa Aurellia Suharno (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Tuberculosis (TB) remains a significant global health burden, particularly in Asia and Africa, which account for the majority of TB cases worldwide. Financing gaps, limited financial protection mechanisms, and dependence on international donors continue to pose major challenges to achieving the 2030 TB elimination targets. Catastrophic costs among households affected by TB remain high, especially in low- and middle-income countries across these regions. Objective: This systematic review aims to assess the effectiveness of TB financing in supporting various TB control program scenarios and its impact on reducing TB incidence in countries across Asia and Africa. Methods: The study was conducted in accordance with PRISMA 2020 guidelines. Literature searches were carried out in four international databases (PubMed, Scopus, ScienceDirect, and ProQuest) for publications from 2014 to 2024. Of the 2,227 identified articles, 29 studies met the inclusion criteria. The included studies comprised economic evaluations (cost-effectiveness and cost-utility analyses), cohort studies, randomized controlled trials, and cross-sectional studies. Methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Results: The synthesis indicates that TB financing from multiple sources—such as central government Commercial License, which permits unrestricted non-commercial use, distribution, and reproduction in any medium provided the original work is properly cited.budgets and international donors (Global Fund, WHO, USAID, UNICEF, Global Drug Facility/GDF, TB REACH/Stop TB Partnership, PEPFAR, the Bill and Melinda Gates Foundation, the UK Department for International Development), as well as World Bank loans—has supported the implementation of various TB control strategies. These include shorter treatment regimen trials in India, incentive-based active case finding in Pakistan, and community-based care models in South Africa. Such financing mechanisms contributed to increased case notification rates, improved treatment success, and reductions in TB incidence. However, catastrophic costs persist, primarily due to income loss and transportation expenses. The sustainability of TB programs in Asia and Africa depends largely on increased domestic financing, strengthened social protection mechanisms, and more efficient fund allocation through strategic purchasing approaches